Voices of Women Entrepreneurs in Tanzania - International Finance Corporation (International Finance Corporation, Washington, DC, 2017)
The Government of Tanzania is committed to supporting women entrepreneurs with both policy and practical support. The Government of Tanzania has made impressive strides in supporting women entrepreneurs, and its policies reflect a commitment to advancing women. The Ministry of Industry, Trade, and Marketing, which commissioned this report, has established special initiatives to reach out to women, and government supported organizations such as the Small Industries Development Organization (SIDO) have been working to empower women entrepreneurs through training and access to credit. One crucial recommendation is to improve women's access to finance by encouraging existing commercial banks to establish gender-sensitive programs and lines of credit for women entrepreneurs. To improve women's access to trade, the report recommends implementing gender analysis in the formulation of trade and economic growth policies, and providing training for women entrepreneurs on international buyer requirements and other relevant information, to facilitate their exports to international markets. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.